Functional outcomes of lower limb reconstruction using vascularised fibula following oncological resection - Amna Kifayatullah; Mamoon Rashid; Sohail Hafeez; Saad Ur Rehman (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the functional outcomes of patients undergoing lower limb reconstruction with vascularised fibula following tumour resection in a tertiary care setting. Method: The single-centre, retrospective, observational study was conducted at the Shifa International Hospital, Islamabad, Pakistan, and comprised data from January 1, 2017, to December 31, 2022, of patients who underwent lower limb reconstruction with vascularised fibula following oncological resection. Functional outcome was assessed using Musculoskeletal Tumour Society score. Data was analysed using SPSS 26. Results: Of the 31 patients with mean age 18.2+9.9 years, 18(58%) were females and 13(42%) were males. Mean follow-up time was 3.8+3.4 years. Mean length of bony defect was 15.3+5.1cm. Mean length of fibular graft harvested was 20.0+5.9cm. The mean Musculoskeletal Tumour Society score was 26.7+2.8. Mean score was higher in foot defects recreated with single barrel fibula 29.3+1.0 compared to tibial defects 27.2+3.3. Minor wound-related complications were encountered in 5(16.1%) patients. Conclusion: Vascularised fibula was found to be an ideal option for the reconstruction of post-oncological treatment defects in the lower limb. Key Words: Lower extremity, Fibula, Free tissue flaps, Limb salvage, Autografts.